2018
DOI: 10.1111/ene.13556
|View full text |Cite
|
Sign up to set email alerts
|

Non‐alcoholic fatty liver disease is associated with stroke severity and progression of brainstem infarctions

et al.

Abstract: These results suggest that NAFLD is a potential risk factor when evaluating the severity and progression of acute BSIs. This relationship is independent of classic risk factors and metabolic syndrome features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 31 publications
(45 reference statements)
3
34
2
1
Order By: Relevance
“…Overall, accumulating evidence points to the presence of an association between NAFLD and stroke risk, severity and outcome. Importantly, NAFLD was present in up to 42.5% of patients admitted with acute ischaemic stroke in these studies . Moreover, NAFLD was diagnosed in these reports with readily available and relatively inexpensive methods (i.e.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Overall, accumulating evidence points to the presence of an association between NAFLD and stroke risk, severity and outcome. Importantly, NAFLD was present in up to 42.5% of patients admitted with acute ischaemic stroke in these studies . Moreover, NAFLD was diagnosed in these reports with readily available and relatively inexpensive methods (i.e.…”
mentioning
confidence: 79%
“…However, that study might have lacked power to detect a significant association. In contrast, a recent retrospective study in patients with brainstem infarction suggested that NAFLD diagnosed with ultrasound is independently associated with more severe stroke and more adverse outcome .…”
mentioning
confidence: 82%
“…The positive association of liver fibrosis on long-term outcomes has also been demonstrated in populations with various comorbidities [5]. Although several previous studies have investigated the association between NAFLD and stroke risk and short-term outcome [9][10][11][12][13], there were no data on the significance of liver fibrosis on long-term outcomes in the stroke population. To our knowledge, this study is the first to show the association between liver fibrosis and long-term mortality in stroke population.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prevalence of liver disease was found to be much higher (63.0-69.2%) among patients with atherosclerotic vascular diseases [19,20]. Previous reports demonstrated that 23.0-42.7% of stroke patients had NAFLD according to laboratory results or abdominal sonography [9][10][11][12][13]. In this study, we used TE, a sensitive and reliable tool to detect even subclinical liver disease, to determine that 32.2% of the patients had liver fibrosis and 41.5% had fatty liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation